Highly Swellable Hydrogels from Waterborne Poly(Vinylamine‐co‐Acetamide). Issue 24 (4th November 2018) - Fischer, Thorsten; Köhler, Jens; Keul, Helmut; Singh, Smriti; Möller, Martin
Abstract: Hydrogels consisting of a hydrophilic polymer backbone are attractive candidates for the formation of superabsorbent hydrogels (SHs). Mainly, such hydrogels are prepared via free radical polymerization. Herein, poly(N‐vinylamine‐ co ‐N‐vinylacetamide) [P(VAm‐ co ‐NVA)] with different amine‐to‐amide ratios are crosslinked with phenyl carbonate telechelic poly(ethylene glycol) (PC‐PEG‐PC) to form a hydrogel in the presence of a base. The structure property relationship in terms of the amide‐to‐amine ratio, the carbonate‐to‐amine ratio, and the base‐to‐amine ratio is investigated by swelling experiments and rheology. 13 C NMR is used to determine the degree of crosslinking which can further influence the swelling behavior and the mechanical properties of the gels. The maximum swelling ratio of the hydrogels is found to be 97 000% with respect to the dry gel, with a storage modulus of 4 kPa of the as‐prepared gel. This swelling behavior of the obtained gels is above the state of the art and has a possibility to be tuned further. Abstract : Poly(N‐vinylamine‐ co ‐acetamide) with different monomer ratios are crosslinked with phenylcarbonate telechelic poly(ethyleneglycol) via carbamate formation in the presence of a base. The crosslinking density is tuned by varying the amine‐to‐amide ratio, amine‐to‐carbonate, and amine‐to‐base ratio and investigated by its effect on the swelling behavior and mechanical properties. Swelling ratios up to 97 000% are obtained.